Frontiers of Jewish scholarship : expanding origins, transcending borders - Albert, Anne O. (Anne Oravetz); Gerber, Noah S., 1976-; Meyer, Michael A. (Jewish culture and contexts., 2022)
"The birth of modern Jewish studies can be traced to the nineteenth-century emergence of the Wissenschaft des Judentums, a movement to promote a scholarly approach to the study of Judaism and Jewish culture. Frontiers of Jewish Scholarship offers a collection of essays examining how Wissenschaft extended beyond its original German intellectual contexts and was transformed into a diverse, global field. From the early expansion of the new scholarly approaches into Jewish publications across Europe to their translation and reinterpretation in the twentieth century, the studies included here collectively trace a path through largely neglected subject matter, newly recognized as deserving attention"--